Identification of novel disease-causing genes in inherited retinal dystrophy - Merepa, SS (2021)
Over 270 genes underlying monogenic forms of inherited retinal dystrophies (IRDs) have been identified to date, enabling the development of new treatment regimens such as gene therapy. However, there are still IRD cases with underlying genetic causes yet to be identified, prompting the need for continued disease-gene identification studies. In this thesis, individuals from four families with dominant IRDs without a known genetic cause underwent whole-exome sequencing (WES). Rare pathogenic variants identified in each family were prioritised for segregation analysis using Sanger sequencing. Variants segregating with the condition in each family were considered as candidate genes and were further characterised for expression, localisation and potential function in the mammalian retina using techniques such as polymerase chain reaction (PCR), western immunoblotting (WB), immunohistochemistry (IHC), site-directed mutagenesis and gene transfection.